ANALYSIS OF VISUAL IMAGE OF SAMSUNG GALAXY S4 ADVERTISEMENTS: A METAFUNCTIONAL APPROACH - -, AHMAD (Jurnal Ilmiah Mahasiswa FIB, 2015)
Key words: Visual Image, metafunction, image, verbal text, advertisement,Samsung Galaxy S4 Advertisement is one of the developing social media in society nowadays. As one of the communicative social media, frequently the society interpret the message differently with the one that the advertiser wants. Therefore, this study is conducted to help the recipient in finding the message that the advertisers try to deliver. There are two objectives in this study, (1) to identify the meaning of image and verbal text of Samsung Galaxy S4 advertisements, and (2) to find out the relation of the image and verbal text in constructing the meaning of Samsung Galaxy S4 advertisements.This study uses qualitative approach because it aims to analyze the meaning of image and verbal text in the advertisements. The writer applies metafunction theory to find the meaning of image and verbal text and also the relation of image and verbal text in constructing the meaning of the Samsung Galaxy S4 advertisements.By applying metafunction theory the writer finds the meaning of the advertisements by elaborating the three functions; Ideational function, interpersonal function, textual function. The result of this study shows that all the elements contain image and verbal text in advertisement are to support the product itself. Besides, it is also considered as the invitation for curiosity of consumer.The writer suggests the next researcher to use the different theory such as semiotics theory, or use different kind of advertisement such as video advertisements. The writer also suggests the advertiser to consider the salience of the product since it will emphasize the product itself.